Malignancy Risk Models for Oral Lesions - Zarate, Ana-María (2013)
Abstract Objectives: The aim of this work was to assess risk habits, clinical and cellular phenotypes and TP53 DNA changes in oral mucosa samples from patients with Oral Potentially Malignant Disorders (OPMD), in order to create models that enable genotypic and phenotypic patterns to be obtained that determine the risk of lesions becoming malignant. Study Design: Clinical phenotypes, family history of cancer and risk habits were collected in clinical histories. TP53 gene mutation and morphometric-morphological features were studied, and multivariate models were applied. Three groups were estabished: a) oral cancer (OC) group (n=10), b) OPMD group (n=10), and c) control group (n=8). Results: An average of 50% of patients with malignancy were found to have smoking and drinking habits. A high percentage of TP53 mutations were observed in OC (30%) and OPMD (average 20%) lesions (p=0.000). The majority of these mutations were GC → TA transversion mutations (60%). However, patients with OC presented mutations in all the exons and introns studied. Highest diagnostic accuracy (p=0.0001) was observed when incorporating alcohol and tobacco habits variables with TP53 mutations. Conclusions: Our results prove to be statistically reliable, with parameter estimates that are nearly unbiased even for small sample sizes. Models 2 and 3 were the most accurate for assessing the risk of an OPMD becoming cancerous. However, in a public health context, model 3 is the most recommended because the characteristics considered are easier and less costly to evaluate.